Variant of rare hermansky — pudlak syndrome associated with granulomatous colitis: diagnostics, clinical course and treatment - Lozynska, L.Y.; Plawski, A.; Lozynska, M.R.; Vytvytskyi, I.; Lozynskyi, R.Y.; Prokopchuk, N.; Tretiak, B. (Experimental Oncology, 2018)
Aim: To study the relationship between the genotype and the phenotype in the patients with Hermansky — Pudlak syndrome (HPS) associated with granulomatous colitis; to monitor clinical course of the disease for adequate treatment, cancer surveillance and genetic counseling. Materials and Methods: The diagnosis of HPS is established by physical examination, chest X-ray, computed tomography, endoscopic examination with biopsy, and laboratory tests, including histology, baseline laboratory blood, urine and feces tests, determination of ASCA-C and ANCA antibodies using an ELISA. Molecular genetic testing for HPS gene mutations, R702W, G908R, L1007fs and P268S mutations in NOD2 gene, and TaqI variant of the VDR gene were carried out. Results: We report 2 cases of HPS from unrelated families. Both were complicated by inflammatory bowel disease with pathologic features of Crohn’s disease refractory to antibiotics and corticosteroids. One patient (family 1) with Ashkenazi Jewish ancestry had pathogenic variant of the HPS-4 gene in exon 8, mutation P268S of NOD2 genes and “Tt” genotype of TaqI variant of the VDR gene. Another patient (family 2) carried two mutations P268S and G908R of NOD2 gene, and had a large paraovarian cyst diagnosed. No consistent success with the standard medical therapy, used for treating granulomatous colitis, associated with HPS, in presented cases was achieved. Patients needed surgical interventions at a young age and a long-term surveillance of the probable development of tumors and other complications. Azathioprine at 2 mg/kg/day and mesalazine 3 g/day were used with some positive effect for prevention of Crohn’s disease postoperative recurrence. Conclusion: The occurrence of perianal lesions, the histopathological findings and the results of the molecular genetic analysis confirmed the mutations P268S and G908R of NOD2 gene in these cases suggest that HPS was truly associated with Crohn’s disease variant with early onset and severe course. The search for the molecular causes of the disease in some individuals may help in the development of new therapeutic and surgical approaches, as well in the improvement of understanding of premalignant inflammatory conditions in a large bowel.